Опыт нелюбви: роман / Анна Берсенева - Берсенева Анна (Русский характер, 2015)
Экземпляры: аб. ЦБ (2017.17.04) / Инвентарный номер: 2963 / Цена: / Авт.знак: Б 51 / ГРНТИ: 17.82 / ББК: 84 (2Рос=Рус)6-44